กระบวนการการเรียนการสอนแบบบูรณาการกับการบริการวิชาการแก่สังคม - กรีเทพ วราพร (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การวิจัยมีวัตถุประสงค์ 1) เพื่อศึกษาและสังเคราะห์กระบวนการการเรียนการสอนแบบบูรณาการกับโครงการบริการวิชาการแก่สังคม 2) เพื่อประเมินผลกระบวนการการเรียนการสอนแบบบูรณาการกับโครงการบริการวิชาการแก่สังคม ประชากรคือ ผู้เชี่ยวชาญ จำนวน 7 คน นักศึกษาสาขาวิชาคอมพิวเตอร์ธุรกิจ จำนวน 49 คน และชุมชนที่เข้าร่วมโครงการบบริการวิชาการ 102 คน ผลการศึกษาระยะ 1 ศึกษากิจกรรมการเรียนให้สอดคล้องกับจุดมุ่งหมายรายวิชา โดยจัดแผนการสอนและประเมินผล ที่มุ่งเน้นการประยุกต์ใช้ความรู้รายวิชากับโครงการฯที่สอดคล้องกับพันธกิจของมหาวิทยาลัย โดยใช้รูปแบบการบริการวิชาการแก่สังคมที่คำนึงถึงความต้องการของชุมชนเป็นหลัก และถ่ายทอดความรู้แบบนักศึกษามีส่วนร่วม ออกแบบกระบวนการโดยมีการประยุกต์ใช้ความรู้ในรายวิชาการกับการจัดการโครงการฯ และดำเนินงานตามกระบวนการ PDCA+S 1) วางแผนงาน (Planning) 2) ปฏิบัติ (Do) 3) ตรวจสอบ (Check) 4) ปรับปรุง (Action) 5) ประยุกต์เทคโนโลยีเพื่องานประชาสัมพันธ์ (Show) ระยะที่ 2 ประเมินความเหมาะสมต่อกระบวนการฯ พบว่า มีความเหมาะสมมากที่สุดทุกด้าน ทั้งในด้านการส่งเสริมศักยภาพนักศึกษา ด้านกระบวนการดำเนินโครงการฯ และด้านกระบวนการเรียนการสอนฯ และชุมชนที่เข้าร่วมโครงการมีความพึงพอใจระดับมากที่สุดต่อการฝึกอบรมการใช้โปรแกรมและการพัฒนาสื่อและการผลิตสื่อวีดิทัศน์เพื่อประชาสัมพันธ์แหล่งท่องเที่ยว หลังจากได้รับบริการทางวิชาการมีความรู้ความเข้าใจเพิ่มขึ้นอย่างมาก สามารถนำความรู้ไปใช้ประโยชน์ส่วนตัวได้มากที่สุด คำสำคัญ: การบูรณาการการเรียนการสอน, การบริการวิชาการแก่สังคม, กระบวนการ PDCA ABSTRACT The research objectives are to synthesize the model of integrating course instruction with academic services to the community and to evaluate the process of integrating instruction with an academic service project to the community. The target group consisted of nine experts. Population was 49 Business Computer students. 7 target community areas provided a total of 102 people population. The results revealed. Phase 1, the process of integrating course was designed in accordance with the course objectives; the lesson plans and assessments were planned to support the use of the course knowledge in carrying out to the community in line with the mission of the university. The services provided to community were mainly based on the needs of the community and aimed at students participatory in services to the community. The academic service project was carried out while integrated with a course instruction. The project implementation was the PDCA+S process: 1) Plan 2) Do 3) Check 4) Act and 5) Show. There are four community groups that want to train computer user and information technology skills. And there were 3 community groups that need knowledge about how to develop and produce video media to promote the tourist attractions in their communities. Phase 2, the suitability in the students’ development aspect, the process was efficient the most suitable. The process of implementing an academic service project was the most suitable. The teaching and learning process integrated with an academic service project was the most suitable. In evaluating the performance the results showed that the trainees and the training on media development and video media production to promote tourist attractions, the trainees were satisfied the most. After receiving academic services, their knowledge and understanding have increased greatly. They can apply the knowledge for their personal use the most. Keywords: Integrated Instruction, Academic Services for the Community, PDCA